Implementation of Human Resource Management in Improving Teacher Work Discipline at State Junior High Schools in North Sumatra - Manullang, Pardomuan; Hutasoit, Romenak (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This research aims to analyze the role of Human Resource Management (HRM) in strengthening teacher work discipline at state junior high schools in North Sumatra, Indonesia. Method: A qualitative descriptive research approach was employed, utilizing in-depth interviews, direct observations, and document review to gather data from school principals, teachers, and education administrators. This method enabled a rich, nuanced exploration of how HRM functions are integrated into school management and their impact on teacher behavior. Practical Applications: Schools can adopt systematic HRM frameworks—such as transparent recruitment, continuous professional development, fair performance appraisal, and equitable reward systems—to foster disciplined work environments. School principals can be trained in transformational leadership to model and enforce discipline effectively. Governments can revise policies to ensure adequate funding, teacher welfare, and flexible hiring practices. Conclusion: The study concludes that effective HRM significantly enhances teacher work discipline through a holistic integration of recruitment, development, evaluation, incentives, and supportive leadership. Success is not solely attributable to individual effort but emerges from systemic alignment between institutional policies, leadership behavior, and organizational culture.